Pemanfaatan Energi Alternatif di SMAN 1 Labuapi - M. Mirmanto; S. Sugiman; A.D. Catur; P. Pandiatmi; N. Nurpatria; S. Syahrul (Universitas Mataram, 2019)
Counselling about the use of alternative energy has been carried out at SMAN 1 Labuapi as a partner. This counselling needs to be done because based on the analysis of the situation, the people around SMAN 1 Labuapi desperately need energy assistance. Meanwhile, in the area around the SMAN 1 Labuapi, there is plenty of alternative energy. Therefore, the main purpose of implementing community service is to motivate the community, especially the community of SMAN 1 Labuapi, to be able to provide their own energy. Then, it is hoped that SMAN 1 Labuapi is expected to provide a model of alternative energy utilization to meet the energy needs of the wider community of Desa Labuapi continuously. The method used in this service is the method of counselling and demonstration about the use of alternative energy. The results of service are changes in the behaviour of the people of SMAN 1 Labuapi to utilize alternative energy. One tool that had been practised was a biogas maker unit using gallons of Narmada.